Draft Five Year Plan 1978-83 Information and Publicity Government of Madhya Pradesh - Planning Commission (Planning Commission, 1978)
A well equipped Publicity Department and Media Publicity Through such an organisation is a must for the fulfillment of the hopes and aspirations of the people in a democratic set up and to acquaint them with the steps taken and objective achieved by their elected representatives in accordance with the directives principles laid down in the constitution of India.
Government of Madhya Pradesh, Planning, Economic and Statistics Department